Principles of educational and psychological measurement and evaluation - Sax, Gilbert. (Wadsworth, 1997)
This book is divided into six parts: Measurement and Evaluation in Education and Psychology; Principles and Methods of Classroom Test Construction; Summarizing and Interpreting Measurements; Criteria for Evaluating Items, Tests, and Measurements; Selecting, Evaluating, and Using Standardized Tests; and Evaluating Students and Programs.